Evaluation of functional group compatibility and development of reaction-accelerating additives in ammonium salt-accelerated hydrazinolysis of amides - Choi, Jeesoo; Nawachi, Anna; Saito, Natsuki; Kondo, Yuta; Morimoto, Hiroyuki; Ohshima, Takashi (Frontiers in Chemistry, 2024)
Functional group compatibility in an amide bond cleavage reaction with hydrazine was evaluated for 26 functional groups in the functional group evaluation (FGE) kit. Accurate and rapid evaluation of the compatibility of functional groups, such as nitrogen-containing heterocycles important in drug discovery research, will enhance the application of this reaction in drug discovery research. These data will be used for predictive studies of organic synthesis methods based on machine learning. In addition, these studies led to discoveries such as the unexpected positive additive effects of carboxylic acids, indicating that the FGE kit can propel serendipitous discoveries.